Effects of l-arginine supplementation on the expression of genes involved with oxidative stress in swine embryos and fetuses - Garcia, Ingrid Soares (2019)
During early gestation in highly prolific gilts, elevated oxidative stress is reported to be associated with pregnancy complications and negatively influence conceptuses development. Arginine is a conditionally essential amino acid and have a known antioxidant capability. In the present work, it was evaluated the effects of 1.0% L- arginine supplementation (ARG) on oxidative stress related genes and proteins of commercial gilts embryos (25 days) and fetuses (35 days). In 25 days of age, there was no statistical difference between the treatments in gene expression. There was a trend of two genes in fetuses from control gilts (CON), SOD2 (P= 0.09) an antioxidant- producing gene and EIF2AK4 (P= 0.07) related with the phosphorylation and activation of nrf2 transcription factor, with activate numerous antioxidant genes in its pathway. Protein abundance also did not present a statistically difference between treatments and in both ages for the nrf2 and sod2 proteins. These results suggest that supplementation of L-arginine in early gestation in gilts (25 and 35 days of age) with the objective to lessen ROS concentrations and oxidative stress damage, is not effective, as in both treatments (ARG and CON), most genes and proteins did not present a significant difference in its performance to maintain a redox homeostasis, and the genes with a trend in its expression did not influence the antioxidant proteins abundance. Keywords: Antioxidants. EIF2AK4. SOD2. Early gestation.